“Wonderful Indonesia”: The Strategy of Indonesia Nation Branding on Tourism Recovery during the Covid-19 Pandemic - Phoebe Inggrid Angeline Romauli; Deasy Silvya Sari (Department of Public Administration, 2023)
The Covid-19 pandemic, which has had a significant impact on international mobility restrictions, has caused the global tourism sector to experience a serious setback. This is also felt in Indonesia, which relies on the tourism sector as a source of income. The Covid-19 pandemic has crippled Indonesia's tourism sector, with thousands of hotels closing and millions of workers threatened to be fired. One way to restore the condition of Indonesian tourism is to convince tourists to keep trusting Indonesian tourism by increasing nation branding in the tourism section, namely Wonderful Indonesia. This research used qualitative methods with data collection through literature review. The author uses the theory of nation branding proposed by Dinnie (2015). This research found that the Government of Indonesia has made efforts to recover the tourism sector by implementing nation branding strategies, namely, conducting Wonderful Indonesia nation branding advertisements through websites, social media, and tourism-related media agencies; doing online branding and social media on Instagram, Facebook, Twitter, TikTok, YouTube, and developing virtual tourism platforms; and then conducting tourism campaigns